The teaching of the Asturian language according to Conceyu Bable. Democracy, autonomy, identity, and linguistic normalization in the Asturias of Transition (1974-1983) - Rodríguez Álvarez, Marcos (Historia y Memoria de la Educación, 2021)
The appearance of Conceyu Bable in 1974, a political-cultural collective of linguistic vindication, marks the beginning of the modern movement for the recovery of the Asturian language. The group broke with the conservationist approach from which the promotion of the Asturian language had been addressed until then, claiming the language as an absolute and unitary code and promoting its social and political normalization. From this perspective the schooling of the language emerged as a priority objective of its normalization. This article tries to unravel the conceptual framework that supported the educational discourse of this movement, as well as the key ideas for the insertion of the Asturian language in the school system that had to adjust to it. School demand revolved around political-cultural as well as educational considerations. Straddling late Francoism and the Transition, the teaching of the language was aired by Conceyu Bable as a democratic, progressive, and autonomous demand. On the other hand, analyzing Asturian reality from the perspective of a sociolinguistic scenario of idiomatic conflict, led the group to recognize the need to extract the native language from its marginalized condition and the rejection in schools that it had historically faced. Conceyu Bable proposed the transformation of the school as a sensitive and respectful space for the expression of the Asturian language and as an instrument capable of transmitting its literacy and knowledge from a scientific approach.